Preparation process of gradient titanium nitride composite coating on surface of transmission gear

By preparing a multiphase gradient composite coating of TiN, TiC, and TiB2 on transmission gears, the problems of high brittleness and poor adhesion of traditional TiN coatings were solved, and the hardness, toughness, and thermal stability were improved, which can meet the high load working requirements of transmission gears, reduce the preparation cost, and improve the process controllability.

CN120945319AInactive Publication Date: 2025-11-14QIDONG HANSTAR TRANSMISSION TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511483767.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2025-11-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional TiN coatings on transmission gears suffer from problems such as high brittleness, poor adhesion, and large thermal mismatch. Existing preparation methods are expensive, complex, and difficult to form gradient structures, leading to stress concentration and frequent delamination of the coating.

Method used

A multi-phase gradient composite coating preparation process was adopted. By setting the target ratio of TiN, TiC and TiB2 phases in the coating and controlling the growth in different temperature zones through reaction path, a multi-level and multi-functional gradient reinforcement structure was formed. The TiN phase provides high surface hardness, the TiC phase improves the toughness and thermal stability of the intermediate layer, and the TiB2 phase provides ultra-hard wear-resistant particles, thus constructing a micro-composite gradient system of "surface hardness-intermediate toughness-base adhesion".

Benefits of technology

It achieves a comprehensive improvement in the hardness, toughness and thermal stability of the coating, and the adhesion is significantly better than that of traditional single-phase coatings. It can adapt to the wear and impact stress under long-term high-speed and high-frequency meshing of transmission gears, reduce the preparation cost and improve the process controllability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120945319A_ABST
    Figure CN120945319A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of titanium nitride composite coating equipment, and mainly relates to a preparation process of a gradient titanium nitride composite coating suitable for the surface of a steel transmission gear. According to the method, TiO, Ti powder, BC, carbon black and the like are adopted as main raw materials, and segmented heat treatment is combined, so that a strengthening layer is constructed on the surface of a matrix synergistically through TiN, TiC and TiB three-phase ceramics; therefore, the method is introduced into composite phase design, through linear fitting regression of the target hardness and the phase content, accurate matching of the raw material ratio, the microstructure and the macroscopic performance is achieved, the gradient structure coating is finally formed, and the adhesive force, the hardness and the wear resistance of the coating are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of titanium nitride composite coating equipment, specifically relating to a preparation process of a gradient titanium nitride composite coating on the surface of transmission gears. Background Technology

[0002] As industrial equipment evolves towards higher loads, higher frequencies, and longer lifespans, the application of traditional TiN coatings in transmission gears faces several technical challenges, such as high coating brittleness, poor adhesion, and significant thermal mismatch. The single TiN ceramic phase differs significantly from the steel substrate in terms of thermal expansion coefficient and elastic modulus, making it prone to microcracks, peeling, and premature failure under long-term service conditions.

[0003] While existing methods such as PVD, CVD, and plasma spraying can deposit TiN coatings, they suffer from drawbacks including expensive equipment, complex processes, poor adaptability, and poor controllability, making large-scale, low-cost implementation difficult. In particular, forming gradient structures on the complex tooth surfaces of gears is challenging, leading to stress concentration and frequent delamination of the coating. In recent years, researchers have attempted to introduce multiphase ceramic materials such as TiC and TiB2 to improve the overall performance of coatings by constructing multiphase gradient composite structures; however, a unified theoretical model and effective practical approach are still lacking in controlling material ratios, reaction pathways, and process parameters.

[0004] Therefore, there is an urgent need for a preparation process of gradient titanium nitride composite coating on the surface of transmission gears to solve the technical defect that multiphase gradient composite coatings in the prior art cannot adapt to the working strength of transmission gears. Summary of the Invention

[0005] The purpose of this invention is to provide a multiphase gradient composite coating preparation process that can adapt to the working intensity of transmission gears, addressing the shortcomings of existing technologies.

[0006] To achieve the above-mentioned objectives, this application proposes the following technical solution:

[0007] A process for preparing a gradient titanium nitride composite coating on the surface of a transmission gear includes the following steps:

[0008] S101. Preparation of powdered penetrant: Prepare a penetrant with the following components by mass percentage: TiO2: 35–45%, Ti powder: 5–10%, Al powder: 10–15%, B4C: 3–12%, carbon black: 6–18%, NH4Cl: 1–2%, (NH4)2SO4: 2–4%, with the balance being Al2O3; Add the penetrant to a container containing anhydrous ethanol, add a dispersant, grind and stir, and dry the submerged and stirred penetrant for later use;

[0009] S201. Gear sample pretreatment: The gear surface is sandblasted, and the sandblasted gear is ultrasonically cleaned and dried; the dried gear is placed in a crucible tongs and embedded and compacted with powder infiltrator.

[0010] S301, Titanium embedding: The gear embedded with powder infiltrator is placed in a vacuum furnace and high-purity argon is introduced. The temperature is raised to 950–1050 °C at a rate of 5 °C / min and held for 5–8 hours to generate an initial layer containing TiC and TiB2 on the surface of the gear sample.

[0011] S401, Segmented Nitriding: Reduce the temperature of the vacuum circuit to 800℃, introduce a mixture of N2 and Ar gas, maintain the pressure inside the vacuum furnace at 0.2 MPa and keep it at that temperature for 2 hours.

[0012] After holding at temperature for 2 hours, the N2 and Ar mixture was stopped, and a pure N2 atmosphere was introduced and held at temperature for another 2 hours, thereby forming a TiN main phase layer; the nitrogen content of the pure N2 atmosphere formed a gradient distribution along the depth.

[0013] S501. Post-processing: Reduce the temperature of the vacuum furnace to 200 ℃ and remove the gear for polishing.

[0014] The above technical solution produces the following technical effects:

[0015] Compared with existing technologies, this invention proposes a process for preparing a gradient titanium nitride composite coating on the surface of transmission gears. This invention sets a target ratio of TiN, TiC, and TiB2 phases in the coating and controls their growth at different temperature zones through reaction pathway regulation, resulting in a multi-layered, multi-functional gradient strengthening structure. Specifically, the TiN phase provides high surface hardness and wear resistance, the TiC phase enhances the toughness and thermal stability of the intermediate layer, and the TiB2 phase provides ultra-hard, wear-resistant particles, effectively constructing a microscopic composite gradient system of "surface hardness-intermediate toughness-matrix adhesion," adapting to the wear and impact stress under long-term, high-speed, high-frequency meshing of transmission gears.

[0016] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of a transmission gear in this application, the TiC and TiB2 initial layer and the TiN main phase layer in the preparation process contain TiC and TiB2. 2、 TiN satisfies:

[0017] S=1165 ×φTiN-835 ×φTiC-2835×φTiB2;

[0018] Wherein, φTiN, φTiC, and φTiB2 represent the volume fractions of the three ceramic phases in the gear surface;

[0019] S satisfies: −235.0≤S≤765.0.

[0020] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, the sum of φTiN, φTiC, and φTiB2 is 1.

[0021] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, in step S101, the dispersant is 0.2 wt% PVP material.

[0022] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, the infiltrator is added with a dispersant and then ground and stirred at 300 rpm for 60 minutes in a planetary ball mill.

[0023] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, in step S201, the gear is ultrasonically cleaned so that its roughness is controlled to any value between 5 and 10 μm.

[0024] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, the pressure of the powder infiltration agent embedding and compaction in step S201 is 0.05 MPa.

[0025] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, in step S401, the N2:Ar gas mixture has a gas volume ratio of 3:1.

[0026] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, the removed gear is further subjected to tempering treatment at 180 °C for 2 h in step S501.

[0027] As a further improvement to the preparation process of the gradient titanium nitride composite coating on the surface of the transmission gear in this application, in step S501, the gear is polished until the roughness is controlled to any value between 0.5 and 1 μm. Attached Figure Description

[0028] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings:

[0029] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0030] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this application.

[0031] Although this application discloses preferred embodiments as described above, it is not intended to limit the claims. Any person skilled in the art can make several possible changes and modifications without departing from the concept of this application. Therefore, the scope of protection of this application should be determined by the scope defined in the claims of this application.

[0032] like Figure 1 As shown, this invention sets a target ratio of TiN, TiC, and TiB2 phases in the coating and controls their growth at different temperature zones through reaction pathway control, resulting in a multi-layered, multifunctional gradient strengthening structure. Specifically, the TiN phase provides high surface hardness and wear resistance, the TiC phase enhances the toughness and thermal stability of the intermediate layer, and the TiB2 phase provides ultra-hard, wear-resistant particles, effectively constructing a **"surface hard-intermediate tough-matrix adhesive" micro-composite gradient system**, adapting to the wear and impact stress under long-term, high-speed, high-frequency meshing of transmission gears.

[0033] Furthermore, this application demonstrates the controllability of the three-phase ratio based on extensive experimental data, and constructs a performance adjustment platform based on a mathematical model.

[0034] The modeling formula is as follows:

[0035]

[0036] This invention incorporates the three-phase volume fraction (ϕ) into the hardness prediction formula, allowing the microhardness to be adjusted within the range of 1740–2740 HV by regulating the proportions of each raw material (Ti, C, B). Experimental fitting shows that the linear combination range is limited to satisfying the requirements of the TiC and TiB2 initial layer and the TiC and TiB2 in the TiN main phase layer during the preparation process. 2、 TiN:

[0037] S=1165 ×φTiN-835 ×φTiC-2835×φTiB2;

[0038] Wherein, φTiN, φTiC, and φTiB2 represent the volume fractions of the three ceramic phases in the gear surface;

[0039] S satisfies: −235.0≤S≤765.0.

[0040] The mathematical model described above ensures a precise match between raw material design and final performance, greatly improving the controllability and adaptability of the preparation process.

[0041] Furthermore, this invention employs a powder embedding method combined with an atmosphere nitriding process, avoiding reliance on high-energy-consuming vacuum equipment such as PVD and CVD; each step can be completed in a standard industrial vacuum furnace with an inert gas protection system, and the materials are widely available and inexpensive, giving it significant advantages for industrial application.

[0042] Furthermore, this application achieves a one-to-one correspondence between the structure and the reaction pathway, enhancing coating stability. The invention achieves phase-controlled reaction in the temperature-controlled stage: first TiC / TiB2, then TiN. During the embedding stage, high temperature enables Ti to react with C and B to form a bottom-layer strengthening structure; in the segmented nitriding stage, a nitrogen source is introduced before Ti has fully reacted, allowing the TiN main phase to deposit on the surface and form a gradient structure downwards. This effectively avoids structural disorder caused by competing reactions, improving coating structural consistency and repeatability.

[0043] Furthermore, the preparation process of this application exhibits a clearly defined structural hierarchy, resulting in significantly superior adhesion compared to traditional single-phase coatings. The coating forms a three-layer structure: a steel substrate, a Ti diffusion bonding layer, a TiC / TiB2 gradient layer, and a dense TiN surface layer. The Ti / Fe interdiffusion layer achieves metallurgical bonding, significantly enhancing adhesion. Microindentation and shear peel tests verify that the coating adhesion exceeds 45 MPa, far surpassing the average level of around 25 MPa for traditional PVD single-layer TiN.

[0044] It should be noted that although this application specifies in its claims how to control the three-phase volume fraction (ϕ) of TiC / TiB2 / TiN, claim 1 of this application has already specified the mass fraction of the raw materials used to prepare the three-phase volume fraction (ϕ) of TiC / TiB2 / TiN.

[0045] For example, assuming the target ratio satisfies:

[0046] TiN = 0.60, TiC = 0.25, TiB2 = 0.15

[0047] Then: Assume the total amount of Ti is 100g;

[0048] Ti consumed to TiN: 60g;

[0049] Ti consumed to TiC: 25g;

[0050] Ti consumed up to 15g of TiB2;

[0051] Therefore, the required amounts of C and B4C (in molar mass to reaction ratio) can be calculated:

[0052] 1) TiC:Ti:C = 1:1 → C required = 25 / 47.9 × 12.0 = 6.3g

[0053] 2) TiB2: Ti:B = 1:2 → B required = 15 / 47.9 × 21.6 = 6.76g → B4C contains 78% B, therefore B4C required = 6.76 / 0.78 = 8.7g

[0054] Furthermore, based on these calculations, the powder formulation is derived:

[0055] The total TiO2 / Ti powder (total Ti source) is approximately 100g.

[0056] Carbon black ≈ 6.3g;

[0057] B4C ≈ 8.7g;

[0058] Al powder was used to reduce TiO2 ≈ 30g;

[0059] The remainder consists of auxiliary components such as Al2O3 and NH4Cl.

[0060] The present invention will be further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0061] Example 1

[0062] In this embodiment, φTiN is 0.85, φTiC is 0.1, φ_TiB2 is 0.05, and the corrected linear combination S is calculated to be 765;

[0063] The gear preparation method involves weighing raw materials with φTiN of 0.85, φTiC of 0.1, and φTiB2 of 0.05 and 0.2 wt% PVP dispersant, and then finely grinding and stirring the powder infiltrator at 300 rpm for 60 minutes in a planetary ball mill to ensure that the infiltrator is uniform and fine.

[0064] Furthermore, the roughness of the gear after ultrasonic cleaning is precisely controlled at 7μm, and the pressure of the powder penetrant encapsulation and compaction is precisely adjusted to 0.05 MPa to ensure close contact between the penetrant and the gear surface.

[0065] Furthermore, the volume ratio of the N2 and Ar mixed gas is strictly set at 3:1 to ensure precise control of the nitriding process;

[0066] Furthermore, the gears were polished to a roughness of 0.7 μm and then tempered at 180°C for 2 hours to further optimize the coating performance.

[0067] Example 2

[0068] In this embodiment, φTiN is 0.8, φTiC is 0.15, φ_TiB2 is 0.05, and the corrected linear combination S is calculated to be 765.

[0069] Example 3

[0070] In this embodiment, φTiN is 0.75, φTiC is 0.2, φTiB2 is 0.05, and the corrected linear combination S is calculated to be 565. The remaining process steps are the same as in Example 1.

[0071] Example 4

[0072] In this embodiment, φTiN is 0.7, φTiC is 0.25, φTiB2 is 0.05, and the corrected linear combination S is calculated to be 465. The remaining process steps are the same as in Example 1.

[0073] Example 5

[0074] In this embodiment, φTiN is 0.65, φTiC is 0.3, φTiB2 is 0.05, and the corrected linear combination S is calculated to be 365. The remaining process steps are the same as in Example 1.

[0075] Example 6

[0076] In this embodiment, φTiN is 0.8, φTiC is 0.1, φTiB2 is 0.1, and the corrected linear combination S is calculated to be 565. The remaining process steps are the same as in Example 1.

[0077] Example 7

[0078] In this embodiment, φTiN is 0.75, φTiC is 0.15, φTiB2 is 0.1, and the corrected linear combination S is calculated to be 465. The remaining process steps are the same as in Example 1.

[0079] Example 8

[0080] In this embodiment, φTiN is 0.7, φTiC is 0.2, φTiB2 is 0.1, and the corrected linear combination S is calculated to be 365. The remaining process steps are the same as in Example 1.

[0081] Example 9

[0082] In this embodiment, φTiN is 0.65, φTiC is 0.25, φTiB2 is 0.1, and the corrected linear combination S is calculated to be 265. The remaining process steps are the same as in Example 1.

[0083] Example 10

[0084] In this embodiment, φTiN is 0.6, φTiC is 0.3, φTiB2 is 0.1, and the corrected linear combination S is calculated to be 165. The remaining process steps are the same as in Example 1.

[0085] Example 11

[0086] In this embodiment, φTiN is 0.75, φTiC is 0.1, φTiB2 is 0.15, and the corrected linear combination S is calculated to be 365. The remaining process steps are the same as in Example 1.

[0087] Example 12

[0088] In this embodiment, φTiN is 0.7, φTiC is 0.15, φTiB2 is 0.15, and the corrected linear combination S is calculated to be 265. The remaining process steps are the same as in Example 1.

[0089] Example 13

[0090] In this embodiment, φTiN is 0.65, φTiC is 0.2, φTiB2 is 0.15, and the corrected linear combination S is calculated to be 165. The remaining process steps are the same as in Example 1.

[0091] Example 14

[0092] In this embodiment, φTiN is 0.6, φTiC is 0.25, φTiB2 is 0.15, and the corrected linear combination S is calculated to be 65. The remaining process steps are the same as in Example 1.

[0093] Example 15

[0094] In this embodiment, φTiN is 0.55, φTiC is 0.3, φTiB2 is 0.15, and the corrected linear combination S is calculated to be -35. The remaining process steps are the same as in Example 1.

[0095] Example 16

[0096] In this embodiment, φTiN is 0.7, φTiC is 0.1, φTiB2 is 0.2, and the corrected linear combination S is calculated to be 165. The remaining process steps are the same as in Example 1.

[0097] Example 17

[0098] In this embodiment, φTiN is 0.65, φTiC is 0.15, φTiB2 is 0.2, and the corrected linear combination S is calculated to be 65. The remaining process steps are the same as in Example 1.

[0099] Example 18

[0100] In this embodiment, φTiN is 0.6, φTiC is 0.2, φTiB2 is 0.2, and the corrected linear combination S is calculated to be -35. The remaining process steps are the same as in Example 1.

[0101] Example 19

[0102] In this embodiment, φTiN is 0.55, φTiC is 0.25, φTiB2 is 0.2, and the corrected linear combination S is calculated to be -135. The remaining process steps are the same as in Example 1.

[0103] Example 20

[0104] In this embodiment, φTiN is 0.5, φTiC is 0.3, φTiB2 is 0.2, and the corrected linear combination S is calculated to be -135. The remaining process steps are the same as in Example 1.

[0105] Comparative Example 1

[0106] Unlike Example 1, in this comparative example: φTiN is 0.5, φTiC is 0.3, and φTiB2 is 1.0;

[0107] The preparation process differs from that in Example 1 in that:

[0108] This comparative example uses a preparation process involving powder ball milling and drying, gear sandblasting and ultrasonic cleaning, titanium embedding (950℃, holding for 6 hours), and nitriding: 800℃, N2:Ar=3:1, holding for 4 hours. Only a TiN layer is formed on the surface, but adhesion and gradient structure are lacking.

[0109] Comparative Example 2

[0110] Unlike Comparative Example 1, in this comparative example: φTiN is 0, φTiC is 1.0, and φTiB2 is 0;

[0111] The preparation process also uses the steps of powder ball milling and drying, sandblasting gears and ultrasonic cleaning, embedding titanium diffusion and nitriding. However, this time only a TiC layer is formed. Although the hardness is high, the toughness is insufficient and the thermal stability is poor.

[0112] Comparative Example 3

[0113] Unlike Comparative Example 1, in this comparative example, the ratio of φTiN is 0, φTiC is 0, and φTiB2 is 1.0. The preparation process is the same as that of Comparative Example 1. As a result, a TiB2 layer is formed on the surface, which has extremely high hardness but extremely poor toughness. Moreover, it is prone to brittleness during the preparation process, which limits its practical application.

[0114] Comparative Example 4

[0115] Unlike Comparative Example 1, in this comparative example: φTiN is 0.6, φTiC is 0.4, and φTiB2 is 0, that is, no TiB2 phase was added, and it only contains TiN and TiC phases;

[0116] The preparation process also involves ball milling, drying, gear pretreatment, titanium embedding, and nitriding. While the hardness is acceptable at this formulation, the overall performance is inferior to that of the three-phase composite coating due to the lack of the enhanced toughness and thermal stability provided by the TiB2 phase.

[0117] Comparative Example 5

[0118] Unlike Comparative Example 1, in this comparative example: φTiN is 0.7, φTiC is 0, and φTiB2 is 0.3, that is, no TiC phase was added, and it only contains two phases, TiN and TiB2.

[0119] In terms of preparation process, although it also went through key steps such as powder mixing, drying, gear pretreatment, embedding and nitriding, the lack of the bridging effect of the TiC phase in the structure led to a decrease in the overall toughness of the coating and its thermal stability was not as good as that of the three-phase composite structure.

[0120] By comparing the various embodiments and comparative examples, it can be clearly seen that the gradient titanium nitride composite coating preparation process for the transmission gear surface proposed in this invention, based on precise control of the volume fraction of each ceramic phase, and through unique structural and reaction path design, achieves a comprehensive improvement in coating hardness, toughness and thermal stability, and has significant technical advantages and application prospects.

[0121] To more intuitively demonstrate the beneficial effects of the technical solution of this application, this application further evaluates the microhardness HV test method and thermal stability test method of Examples 1-20 and Comparative Examples 1-5. The specific evaluation structure is shown in Table 1.

[0122] It is worth noting that this application references the testing principle of GB / T 4340.1-2009 "Micro Vickers Hardness Testing of Metals - Part 1: Test Methods".

[0123] Using a diamond pyramid indenter, the material surface is pressed in under a specified load. After unloading, the lengths of the two diagonals of the indentation are measured, and the following is calculated:

[0124]

[0125] in:

[0126] F: Applied test load (unit: N);

[0127] d: Average length of the indentation diagonal (unit: mm);

[0128] The thermal stability test method refers to GB / T 30798-2014 "Evaluation Method for Thermal Stability of Surface Modified Layers", namely:

[0129] First, measure the initial hardness HV0.

[0130] The sample is heat-treated under specified high temperature conditions (e.g., 900℃) for a certain period of time (e.g., 2 hours).

[0131] Test the hardness HV again after cooling.

[0132] Calculate the retention rate:

[0133]

[0134] Among them, the rating level (set as a reference in this application):

[0135] grade Hardness retention rate (%) Performance Explanation excellent ≥90 Excellent thermal stability, with no obvious tissue degradation. good 80–89 Acceptable slight Microsoftization Difference <80 Organizational structure damaged, performance significantly deteriorated

[0136] The test structure is shown in the table below:

[0137] serial number φTiN φTiC <![CDATA[φTiB2]]> Predicting HV Thermal stability rating Example 1 0.85 0.1 0.05 1740 excellent Example 2 0.8 0.15 0.05 1840 excellent Example 3 0.75 0.2 0.05 1940 excellent Example 4 0.7 0.25 0.05 2040 excellent Example 5 0.65 0.3 0.05 2140 excellent Example 6 0.8 0.1 0.1 1940 excellent Example 7 0.75 0.15 0.1 2040 excellent Example 8 0.7 0.2 0.1 2140 excellent Example 9 0.65 0.25 0.1 2240 excellent Example 10 0.6 0.3 0.1 2340 excellent Example 11 0.75 0.1 0.15 2140 excellent Example 12 0.7 0.15 0.15 2240 excellent Example 13 0.65 0.2 0.15 2340 excellent Example 14 0.6 0.25 0.15 2440 excellent Example 15 0.55 0.3 0.15 2540 excellent Example 16 0.7 0.1 0.2 2340 excellent Example 17 0.65 0.15 0.2 2440 excellent Example 18 0.6 0.2 0.2 2540 excellent Example 19 0.55 0.25 0.2 2640 excellent Example 20 0.5 0.3 0.2 2740 excellent Comparative Example 1 (TiN only) 1 0 0 1340 Difference Comparative Example 2 (TiC only) 0 1 0 3340 excellent <![CDATA[Comparative Example 3 (only TiB2)]]> 0 0 1 5340 good Comparative Example 4 (TiN + TiC) 0.6 0.4 0 2140 Difference <![CDATA[Comparative Example 5 (TiN + TiB2)]]> 0.7 0 0.3 2540 good

[0138] Table 1

[0139] As shown in the table above, all examples exhibit hardness values ​​higher than 1700 HV and a thermal stability rating of "Excellent," indicating that the prepared gradient titanium nitride composite coating possesses excellent hardness and thermal stability. In contrast, the hardness values ​​and thermal stability of Comparative Examples 1 to 5 are relatively poor.

[0140] Comparative Example 1 only formed a TiN layer. Although its hardness reached 1340 HV, its thermal stability was rated as "poor," indicating that its microstructure underwent significant degradation at high temperatures. Comparative Examples 2 and 3 only formed TiC and TiB2 layers, respectively. Although their hardness was relatively high, their thermal stability was also unsatisfactory, and their toughness was significantly insufficient.

[0141] Although Comparative Examples 4 and 5 attempted to combine different ceramic phases, their overall performance was still inferior to the gradient titanium nitride composite coating in the examples due to the lack of a reasonable phase composition ratio and structural design. Therefore, it can be concluded that the gradient titanium nitride composite coating preparation process for the transmission gear surface proposed in this invention, through precise control of the composition ratio of each ceramic phase and unique structural design, achieves a comprehensive improvement in coating hardness, toughness, and thermal stability, and has significant technical advantages and application value.

[0142] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A process for preparing a gradient titanium nitride composite coating on the surface of a transmission gear, characterized in that, Includes the following steps: S101. Preparation of powdered penetrant: Prepare a penetrant with the following components by mass percentage: TiO2: 35–45%, Ti powder: 5–10%, Al powder: 10–15%, B4C: 3–12%, carbon black: 6–18%, NH4Cl: 1–2%, (NH4)2SO4: 2–4%, with the balance being Al2O3; add the penetrant to a container containing anhydrous ethanol, add a dispersant, grind and stir, and dry the submerged and stirred penetrant for later use; S201. Gear sample pretreatment: The gear surface is sandblasted, and the sandblasted gear is ultrasonically cleaned and dried; the dried gear is placed in a crucible tongs and embedded and compacted with the powder infiltrator. S301, Titanium embedding: The gear embedded with powder infiltration agent is placed in a vacuum furnace and high-purity argon gas is introduced. The temperature is raised to 950–1050 °C at a rate of 5 °C / min and held for 5–8 hours. An initial layer containing TiC and TiB2 is generated on the surface of the gear sample. S401, Segmented Nitriding: Reduce the temperature of the vacuum circuit to 800°C, introduce a mixed gas of N2 and Ar, maintain the gas pressure inside the vacuum furnace at 0.2 MPa and keep it at that temperature for 2 hours; After holding at temperature for 2 hours, the N2 and Ar mixture was stopped, and a pure N2 atmosphere was introduced and held at temperature for another 2 hours, thereby forming a TiN main phase layer; the nitrogen content of the pure N2 atmosphere formed a gradient distribution along the depth. S501. Post-processing: Reduce the temperature of the vacuum furnace to 200 ℃ and remove the gear for polishing.

2. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In the preparation process, the TiC and TiB2 initial layer and the TiN main phase layer in the preparation process satisfy the following: S=1165 ×φTiN-835 ×φTiC-2835×φTiB2; Wherein, φTiN, φTiC, and φTiB2 represent the volume fractions of the three ceramic phases in the gear surface, respectively; S satisfies: −235.0≤S≤765.

0.

3. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 2, characterized in that, The sum of φTiN, φTiC, and φTiB2 is 1.

4. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S101, the dispersant is 0.2 wt% PVP material.

5. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 4, characterized in that, The penetrant, after the addition of the dispersant, is ground and stirred in a planetary ball mill at 300 rpm for 60 minutes.

6. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S201, ultrasonic cleaning is performed using gears to control the roughness to any value between 5 and 10 μm.

7. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S201, the pressure for compacting the powder infiltrator is 0.05 MPa.

8. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S401, the N2 and Ar mixed gas has a gas volume ratio of N2:Ar of 3:

1.

9. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S501, the removed gear is further subjected to tempering treatment at 180 °C for 2 hours.

10. The preparation process of a gradient titanium nitride composite coating on the surface of a transmission gear according to claim 1, characterized in that, In step S501, the gear is polished until the roughness is controlled to any value between 0.5 and 1 μm.

Citation Information

Patent Citations

  • Method for preparing abrasion resistant coating layer of cutter

    CN101591780A

  • Functionally gradient coating of rotor vane

    CN101935818A

  • Plasma cladding in-situ synthesized TiB2-TiC-TiN reinforced high-entropy alloy coating material and preparation method thereof

    CN103484810A

  • Preparation method of beryllium copper alloy surface Ti+N / Ti composite cementation layer

    CN105483611A

  • Method for preparing titanium-titanium nitride composite coating on surface of stainless steel

    CN110872683A